The Degree of Availability of Professional Teaching Competencies for Physical Education Teachers in Jordan - Mohammad Omar AL-Momani; Randa Saleh Jawarneh (Jurnal Pendidikan Kesehatan Rekreasi, 2022)
Given the importance of the teacher’s role in the classroom ; Educational institutions have been keen to rehabilitate and train him to carry out the tasks entrusted to him, whether before service through programs and courses offered in institutes and universities, or during service through training courses with the aim of developing many of his skills so that he possesses a set of educational competencies that he needs to transfer educational experiences Therefore, this study came, which aimed to identify the degree of availability of professional teaching competencies for physical education teachers in Jordan from their point of view and its relationship to some variables such as gender, academic qualification and years of experience, where the descriptive approach was used in addition to The questionnaire consisting of (40) paragraphs and distributed into four areas as a tool for the study. The study sample consisted of (784) male and female teachers in the second semester of the year (2021/2022) ; The study concluded that the degree of availability of professional teaching competencies was moderately in all fields of study, in addition to the absence of statistically significant differences that are attributed to the variables of gender and educational qualification, and the presence of statistically significant differences due to the variable years of experience and in favor of teachers with experience of more than 10 years.